Property Prices and Real Estate Financing in a Turbulent World - Morten Balling; Christian Sinding Bentzen; Jesper Berg; Alan Boyce; Per Callesen; José Carrasco-Gallego; Giovanni Dell'Ariccia; R. Glenn Hubbard; Deniz Igan; Marius Jurgilus; Kevin J. Lansing; Ronan Lyons; et al. (SUERF - The European Money and Finance Forum, 2013)
On 15th November 2012 in Copenhagen, SUERF and Nykredit in association with Danmarks Nationalbank organised a conference on “Property prices and real estate financing in a turbulent world.” The papers included in this SUERF Study are based on contributions to the conference.
Keywords: G21; R21; R31; R38; 330; Housing bubbles; housing prices; household debt; commercial real estate; United Kingdom; Real estate booms; bubbles; financial and macroeconomic stability; Real estate credit; monetary policy; welfare; DSGE; LTV; Ireland; housing market cycle; property ladder; amenity prices; foreclosures; Norway; United States; Mortgages; EU; mortgage models; housing-related debt; Accelerated amortization; mortgage delinquency; refinancing; impact to tax payers; Immobilienpreis; Spekulationsblase; Finanzkrise; Immobilienfinanzierung; Welt